Human gut microbiota in health and disease: Unveiling the relationship - Afzaal, Muhammad; Saeed, Farhan; Shah, Yasir Abbas; Hussain, Muzzamal; Rabail, Roshina; Socol, Claudia Terezia; Hassoun, Abdo; Pateiro, Mirian; Lorenzo, José M.; Rusu, Alexandru Vasile; Aadil, Rana Muhammad (Frontiers in microbiology, 2022)
The human gut possesses millions of microbes that define a complex microbial community. The gut microbiota has been characterized as a vital organ forming its multidirectional connecting axis with other organs. This gut microbiota axis is responsible for host-microbe interactions and works by communicating with the neural, endocrinal, humoral, immunological, and metabolic pathways. The human gut microorganisms (mostly non-pathogenic) have symbiotic host relationships and are usually associated with the host’s immunity to defend against pathogenic invasion. The dysbiosis of the gut microbiota is therefore linked to various human diseases, such as anxiety, depression, hypertension, cardiovascular diseases, obesity, diabetes, inflammatory bowel disease, and cancer. The mechanism leading to the disease development has a crucial correlation with gut microbiota, metabolic products, and host immune response in humans. The understanding of mechanisms over gut microbiota exerts its positive or harmful impacts remains largely undefined. However, many recent clinical studies conducted worldwide are demonstrating the relation of specific microbial species and eubiosis in health and disease. A comprehensive understanding of gut microbiota interactions, its role in health and disease, and recent updates on the subject are the striking topics of the current review. We have also addressed the daunting challenges that must be brought under control to maintain health and treat diseases.